2008
DOI: 10.1086/590408
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional Full Particle Simulation of a Perpendicular Collisionless Shock with a Shock-Rest-Frame Model

Abstract: A two-dimensional (2D) shock-rest-frame model for particle simulations is developed. Then full kinetic dynamics of a perpendicular collisionless shock is examined by means of a 2D full particle simulation. We found that in the 2D simulation there are fewer nonthermal electrons due to surfing acceleration which was seen in the previous 1D simulations of a high Mach number perpendicular shock in a low-beta and weakly magnetized plasma. This is because the particle motion along the ambient magnetic field disturbs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Early 1D simulations (Quest 1985;Lembege & Dawson 1987) and recent 2D simulations (Umeda et al 2008(Umeda et al , 2009(Umeda et al , 2014Wieland et al 2016) indicated that supercritical perpendicular shocks become nonstationary and undergo cyclic self-reformation. Therefore, all instabilities driven by reflected ions in the foot region will also evolve in a nonstationary way, and the conditions for the Buneman-wave growth and efficient SSA will probably be met only at certain locations and time periods.…”
Section: Introductionmentioning
confidence: 99%
“…Early 1D simulations (Quest 1985;Lembege & Dawson 1987) and recent 2D simulations (Umeda et al 2008(Umeda et al , 2009(Umeda et al , 2014Wieland et al 2016) indicated that supercritical perpendicular shocks become nonstationary and undergo cyclic self-reformation. Therefore, all instabilities driven by reflected ions in the foot region will also evolve in a nonstationary way, and the conditions for the Buneman-wave growth and efficient SSA will probably be met only at certain locations and time periods.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed initial setup is described in Refs. 31,32 . In the present study, we assume a low-Mach number (M A ∼ 6), moderate beta (β i1 = β e1 = 0.32), weakly-magnetized (ω pe1 /ω ce1 = 4), and perpendicular (θ Bn = 90…”
Section: Simulation Setupmentioning
confidence: 99%
“…We developed a new method for exciting collisionless shocks in kinetic plasma simulations, where the simulation system is taken in the shock rest frame [5][6][7]. The new method allows us to study longer-time development of collisionless shocks on a limited computer resource.…”
Section: Methodsmentioning
confidence: 99%